Student Interaction with Moodle Activities: a Study Based on Web Mining - Muñoz-Gea, Juan Pedro; Pérez de la Cruz, Francisco Javier; Busquier Sáez, Sonia; Silva Pérez, María Magdalena; Angosto Hernández, Carlos (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
The purpose of this article is to analyze the learning data set obtained from the Moodle platform andtrack student activity as an essential requirement for this new teaching-learning interactive in implementing the European Higher Educa-tion Area (EHEA) has been a substantial changes in the assessment process. The various web mining subjects used as a methodology to extract information using variables that provide information about how students interact with different activities configured in the virtual platform Moodle and monitoring that make the subject taking into temporary variables account. This is evidenced by the results that systems for managing learning, Learning Management System (LMS) in the form of virtual learning platforms store large amounts of information that can be drawn from the various subjects under interactuaciones with the virtual platform Moodle. We conclude that there is a relationship between interactions with Moodle and academic performance, and the use of students and teachers from the platform.